Arthroscopic Excision of Intra-Articular Osteoid Osteoma at the Elbow - Taku Hatta; Masami Hosaka; Munenori Watanuki; Toshihisa Yano; Shinichirou Yoshida; Mika Watanabe; Shin Hitachi; Eiji Itoi (Case Reports in Orthopedics)
Osteoid osteoma (OO) apparent in the intra-articular region of the elbow is very rare. Although computed tomography-guided excision and radiofrequency ablation have been recognized as useful treatment options, arthroscopic excision has recently received focus as an alternative strategy for lesions close to neurovascular structures or intra- and juxta-articular lesions. We herein report a 17-year-old female who underwent arthroscopic treatment for intra-articular OO located at the olecranon/coronoid fossa. Her symptoms included elbow pain that was exacerbated at night and contracture of elbow flexion-extension, and she was diagnosed with intra-articular OO after 12 months of symptomatic history. Arthroscopically, thorough synovectomy for both the anterior and posterior aspects of the joint enabled definition of the tumor margin with hyperemic alteration and excision of the lesion as an en bloc specimen. At the 12-month follow-up, the patient had no recurrence of elbow limitation or pain. This case report describes the advantages of arthroscopic treatment, including a low-invasive approach and easy accessibility to the whole intra-articular space, which can provide clear visualization of the tumorous lesion.